Seleksi Fenotipe Populasi Padi Gogo untuk Hasil Tinggi, Toleran Alumunium dan Tahan Blas di Tanah Masam - Mulyaningsih, Enung Sri; Perdani, Ambar Yuswi; Indrayani, Sri; Suwarno, Suwarno (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
The aims of research is to get upland rice lines with high yield, aluminum tolerance and resistance of blast. Genetic material were used 380 lines (F6) from six hybridization combination were evaluated under stress Al condition in environment endemic blast by using augmented design with five randomized block. Performance of lines at the field and level of tolerance was tested.Â The results showed that have five genetic clusters formed of 380 lines of upland rice in a test based on a quantitative character. The best cluster is cluster number 3 with lines that have characters growth vigor of plants are uniform, 50% floweringÂ days short, harvesting of early maturing, high plant medium, amount of productive tillers is high, medium on panicle length, the most number of filled grain, the lowest of empty grains, the most weight of 5 panicles and high yield potential. Aluminum Tolerant and Blast Resistant owned by almostÂ all clusters. But the lines on the cluster 3 have highest resistance to blast and Al at 96%.